Studies on the pathogenesis and epidemiology of ovine pulmonary adenocarcinoma (OPA) - Salvatori, Daniela (The University of Edinburgh, 2005)
Ovine pulmonary adenocarcinoma (OPA) is a contagious lung cancer of sheep. OPA is found in over 20 countries on the continents of Europe, Africa, America and Asia, and in a wide variety of breeds. The tumour also has been diagnosed sporadically in goats and wild moufflon. OPA is caused by an exogenous beta-retrovirus, jaagsiekte sheep retrovirus (JSRV), which is different from the transcriptionally active endogenous retroviral sequences present in the ovine genome. A unique feature of OPA is the absence of a specific humoral immune response to JSRV, despite the highly productive infection in the lungs and the disseminated lymphoid infection. The absence of detectable antibodies has hampered the diagnosis and control of the disease before the development of clinical signs. The disease can be reproduced consistently in neonatal lambs by intra-tracheal injection of inocula containing JSRV, but this experimental model was unsuitable for various purposes, such as the assessment of potential vaccine preparations. In the present study, the clinical disease was reproduced, pathologically confirmed as OPA, in a high proportion of lambs inoculated intra-tracheally with infectious lung fluid at either one, three or six months of age. The incubation periods, however, were found to be longer in the older age groups than in one week old lambs. During the course of the experiment, viraemia was detected consistently by PCR (JSRV U3 PCR). The persistent viraemia and the delayed development of OPA in the older lambs paralleled epidemiological observations in naturally affected flocks. The optimisation of the JSRV U3 PCR represented an important breakthroughs for studies on the pathogenesis of this infection and for the diagnosis and control of the disease. JSRV U3 PCR was employed for the first longitudinal survey for detecting JSRV infection in a flock with natural history of OPA. Ewes and offspring were followed for a period of two and half years and the JSRV U3 PCR test was repeated every 3-4 months. It was shown that the flock was heavily infected with JSRV. The lambs from both negative and positive mothers became JSRV positive as early as 20-30 days after birth. The rate of infection of the ewes and of the lambs increased significantly after the first test. JSRV incidence in the ewe population was higher in the period prior to lambing. The results suggested that Texel breedline had a higher susceptibility to JSRV infection and a higher probability ofremaining positive.

New envelope and capsid recombinant proteins were produced not only for immunological assays but also for preliminary immunisation trials in sheep. The present experiments have been able to overcome previous difficulties regarding JSRV Env protein production.

In the present study IHC gave new insight about histogenesis and viral pathogenesis of OPA. In fact SU Env protein was found widespread on the surface of tumour cells. This finding proved that envelope protein is consistently produced suggesting again a role in cell proliferation. These epidemiological and experimental transmission data point to JSRV as a non-acute transforming retrovirus and raise questions about the in vivo role of JSRV env gene in transformation.